Investment Commitments and the Number of New Projects Decline in the Middle East and North Africa - Izaguirre, Ada Karina; Perard, Edouard (World Bank, Washington, DC, 2012)
Private activity in infrastructure in the Middle East and North Africa declined sharply in 2008, according to just-released data from the Private Participation in Infrastructure Project database. Both investment commitments and the number of new projects declined, in both the first and second half of the year. Existing telecommunications operators accounted for most of the annual investment. The region's share of total investment commitments in developing countries in 2008 was less than 4 percent, down significantly from its 7.3 percent share in 2007. In 2008, 10 infrastructure projects with private participation reached financial or contractual closure in six low- or middle-income countries in the region. These involve investment commitments (hereafter, investment) of US$2.4 billion. Infrastructure projects implemented in previous years had additional commitments of US$3.6 billion, bringing total investment in 2008 to US$6 billion. This level represented a 49 percent drop from that in 2007 and was the lowest since 2003.